POTENSI PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KOTA BENGKULU - Susena, Karona Cahya (JURNAL EKOMBIS REVIEW, 2015)
Karona Cahya Susena; The purpose of this study was to determine the potential revenue projections Land and Building Tax (PBB) in the city of Bengkulu years 2014-2016. This type of research used in this research is quantitative. The benefits of this research are as information material to the Regional Government of Bengkulu in policy making and management of land and building tax (PBB) in 2014 up to 2016. This study suggests that projected revenue potential land and building tax (PBB) in the city of Bengkulu experience increase from 2014 to 2016. The amount of potential revenue Land and Building Tax (PBB) in the city of Bengkulu year in a row from 2014 to 2016 as follows: 2014 by Rp12.285.612.144, 2015 by Rp12.852.211.071, 2016 by Rp.13.418.809.999, increased revenue potential land and building tax (PBB) will lead to greater realization of the UN acceptance for the city of Bengkulu in the next three years.Key words: Land and Building Tax